Fatigue in Kidney Transplantation: A Systematic Review and Meta-Analysis - Maurizio Bossola; Maria Arena; Federica Urciuolo; Manuela Antocicco; Gilda Pepe; Giovanna Elisa Calabrò; Claudia Cianfrocca; Enrico Di Stasio (Diagnostics, 2021)
Fatigue is still present in up to 40–50% of kidney transplant recipients (KTR), the results of studies comparing the prevalence among patients on hemodialysis (HD) and KTR led to conflicting results. Fatigue correlates include inflammation, symptoms of depression, sleep disorders and obesity. Fatigue in KTR leads to significant functional impairment, it is common among KTR poorly adherent to immunosuppressive therapy and is associated with a serious deterioration of quality of life. The following databases were searched for relevant studies up to November 2020: Medline, PubMed, Web of Science and the Cochrane Library. Several studies have compared the prevalence and severity of fatigue between KTR and hemodialysis or healthy patients. They have shown that fatigue determines a significant functional deterioration with less chance of having a paid job and a significant change in quality of life. The aim of the review is to report methods to assess fatigue and its prevalence in KTR patients, compared to HD subjects and define the effects of fatigue on health status and daily life. There is no evidence of studies on the treatment of this symptom in KTR. Efforts to identify and treat fatigue should be a priority to improve the quality of life of KTR.